New insights into the role of the oral leukoplakia microenvironment in malignant transformation - González-Arriagada, Wilfredo Alejandro; Canedo-Marroquin, Gisela; Adorno-Farías, Daniela; Fernández-Ramires, Ricardo (Frontiers in Oral Health, 2024)
Oral leukoplakia is the most frequent potentially malignant lesion of the oral cavity. Dysplasia grading is the main factor to assess the risk assessment, but challenges persist to determine the exact risk of transformation, and the literature have been focused to study alternative biomarkers. The interaction between dysplastic epithelial cells and the microenvironment initiates early, and the communication is mainly mediated by lymphocytes, inflammation factors, fibroblasts, and extracellular matrix, leading to the dysplastic progression. Leukoplakia-infiltrating leukocytes (LILs) and leukoplakia-associated fibroblasts (LAFs) play crucial roles in the dysplastic microenvironment. Immune response is related to intraepithelial T lymphocytes infiltration, mechanisms of immunosuppression coordinated by regulatory T cells, M2 macrophage polarization and an increasing number of Langerhans cells, while fibroblastic and extracellular matrix factors are related to an increasing number of pro-tumorigenic myofibroblasts, increasing expression of metalloproteinases versus reduction of TIMPs, and increasing expression of chemokines and other inflammatory mediators. The microenvironment offers insights into leukoplakia progression to carcinoma and understanding the complexity of the oral potentially malignant disorders microenvironment aids to determine the malignant transformation risk and to propose new therapeutic alternatives.